DEFINITION OF A FAMILY IN LEGAL SCIENCE - Тімуш, Ірина Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article provides a scientific and theoretical analysis of the concept of «family» in legal science, provides a comparative analysis of the concept of «family», taking into account the specificity of family-marital relations. Methods: the essence of the concept of «family» is analyzed in such directions as: the key category, the basis of creation, the purpose, the result. Discussion: theoretical and methodological aspects of the concept of «family» are analyzed. The official statistical information characterizing protection of rights and interests of subjects of family law is analyzed. The tendencies of the processes of marriage and divorce as a sphere of family law are determined. The conclusion is made on the need to ensure the principles, guarantees of family law in civil, criminal, administrative aspects. Discussed the problem of interpreting the concept of «family» in the social and legal sense.